Percepção dos impactos causados por ruídos de geradores eólicos no estado do Piauí - Araújo, Rômulo Diniz (2024)
The installed capacity of wind energy has been growing all over the world. In 2023 it reached 1 TW of power in operating. According to the World Wind Energy Council, the forecast is 2 TW by 2030. The expansion of wind energy has brought benefits, but at the same time, many conflicts have arisen over the implementation of wind farms, especially Around rural communities. One of the main impacts in wind farms is the noise. The objectives of this research are to understand the community's responses to the effects of noise from wind generators and the acceptance or rejection of the implementation of the wind farm from the perspective of procedural and distributive justice in the Community of Serra dos Pereiros, in the municipality of Caldeirão Grande do Piauí - PI. The survey mapped the residences using the QGIS program. Five noise monitoring points were chosen to identify homes near one or more wind turbines. Sound pressure levels were measured using a DB 200 decibel meter. Questionnaires were administered to 69 residents using statistical sampling techniques. To understand the community's perception of noise nuisance and their acceptance or rejection of the wind farm. The questionnaire is an adaption from research carried out in Brazil and South Korea. In this wind farm, there are 144 houses and 24 wind turbines within the perimeter of 5 wind farms. Only one house is less than 150 m from a wind tower. But, there are 7 houses are between 150 and 200 m away, 30 houses are between 200 and 300 m away, and 35 houses are between 300 and 400 m away. There was a densification of homes within 400 m of the wind turbine towers, with around 50% of homes within this perimeter. Regarding the noise analysis, all the continuous equivalent sound pressure level values are above the Evaluation Criteria Level, and the wind turbines contribute to the increase in noise. In the data processing analysis procedures, Cronbach's Coefficient was 0.8. Spearman's correlations were calculated for all the variables, confirming moderate and strong correlations in the responses, “change in the landscape”, “opinion on wind farms”, “political process for setting up wind farms”, “fairness of the process” and “compensation”. In the regression models that had the response “perception”, referring to the 2nd dependent variable “my life was affected by the installation of the wind farm”, the response “compensation” was the most influential factor in explaining the perception of wind farms. Regarding noise nuisance, is often it found related to subjective perceptions of wind farms and not to the value of the actual sound level. Another way, regarding the acceptance or rejection of the wind farm, it was found that the Community accepted the project, even though procedural justice did not occur, due to the distribution of some benefits to the community.